Urban Governance, City Politics, and Environmental Collaboration in South Korea: “Saving Taewha River Movement” in Hyundai City" - BAE, Yooil (Institutional Knowledge at Singapore Management University, 2011)
The politics of development for fifty years in South Korea produced two distinctive features of postwar politics: a strong central government and big conglomerates. During most of the development period, the central government and big businesses exercised enormous power over public policy processes without much consideration for localities and citizens. A longstanding urban literature on Korea also confirmed that central politics and business interests were likely to have systemic power over other local political entities.Unlike this conventional wisdom, however, rebirth of local elections in the mid‐1990s followed by decentralization reform in 2000s has remapped local politics in Korea. While central government and big businesses still persist, expanded local executives’ decisional authorities and citizen participation in local affairs have created “local political arena.” Along with this political decentralization, national economic crisis and wave of liberalization have also encouraged further administrative and financial devolution under the democratic administrations.In this transitional context, the case of ‘sustainability movement’ in the city of Ulsan where several Hyundai and other conglomerates’ manufactures such as Hyundai Motors and Hyundai Shipbuilding Co. are located is particularly interesting, since it shows a transition from ‘state‐centered’ city politics to ‘collaborative city governance’ in Korea. In the age of state‐led development, the city’s political agendas were pre‐occupied with developmentalism without consideration for quality of life or sustainability. Therefore, despite the city’s economic prosperity, its air pollution and living environment became one of the worst in Korea. Yet, popularly elected mayoral leadership in Ulsan since the late 1990s has paid attention to post‐industrial aspects of local politics and successfully orchestrated business and citizen participation in improving the city’s environment. By investigating the case of recovering Taewha River of Ulsan in the 2000s, this paper explores how decentralization transformed local governance and how empowered local executives dealt with central government, big business, and citizens who might not have been interested in making ‘environmentally‐friendly city.’